Improve your communication skills, revised second edition [ - Barker, Alan , 1956- (Sunday Times creating success, 2010)
Shows you how to improve your conversations and build rapport with colleagues, hold interviews and staff appraisals, learn the skills of persuasion, give effective presentations, write emails, letters and reports and write for the web